2002
DOI: 10.1097/00007890-200202150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Acute Thrombosis of Renal Transplant Artery

Abstract: Fibrinolysis seems an efficient treatment that may save transplants after up to 24 hr of the arterial occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…[2] Sudden reduction or cessation of urine output is usually the only mode of presentation with no other clinical signs or symptoms to suggest the diagnosis. A very high degree of suspicion is therefore required in early postoperative period to make a timely diagnosis of transplant renal artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Sudden reduction or cessation of urine output is usually the only mode of presentation with no other clinical signs or symptoms to suggest the diagnosis. A very high degree of suspicion is therefore required in early postoperative period to make a timely diagnosis of transplant renal artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of graft salvage in transplant renal artery thrombosis with endovascular catheter directed thrombolysis with or without angioplasty have been reported. [2] More commonly by the time diagnosis is confirmed, it is already too late and graft nephrectomy is the only option left.…”
Section: Discussionmentioning
confidence: 99%
“…However, with early diagnosis and intervention, it is possible to save the kidney [16, 20, 33, 58–60]. Even up to 15–20 hours after onset of symptoms, salvage has been reported [61, 62]. Flow in the occluded vessel can be reestablished by open surgery with urgent thrombectomy [16, 33].…”
Section: Graft Salvage Is Possiblementioning
confidence: 99%
“…These studies reported successful reperfusion in most patients without significant therapy-associated complications. However, renal outcomes were only improved in some patients [ 26 – 31 ]. Angioplasty is the used treatment among patients with renal infarction caused by an intrinsic abnormality of renal vessels, such as dissection, angioplasty with stent placement.…”
Section: Discussionmentioning
confidence: 99%